2009
DOI: 10.1590/s1516-35982009001100003
|View full text |Cite
|
Sign up to set email alerts
|

Dose inseminante para fertilização artificial de ovócitos de dourado

Abstract: RESUMO -Objetivou-se determinar a dose inseminante adequada para uso na fertilização artificial de ovócitos de dourado (Salminus brasiliensis). Os ovócitos foram distribuídos em delineamento inteiramente casualizado, e fertilizados com uma das relações espermatozoides/ovócito 6,0×10 3 ; 6,0×10 4 ; 6,0×10 5 ; 6,0×10 6 ou 3,0×10 7 , cada uma com quatro repetições.Considerou-se unidade experimental uma incubadora de volume útil de 2,5 L, contendo 2,0 mL de ovócitos não-hidratados.As taxas de fertilização foram me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 31 publications
1
18
1
5
Order By: Relevance
“…Após a ativação, 5 μL do material foram analisados em microscopia de luz (objetiva 40X), registrando-se o tempo transcorrido até a perda do movimento de 50% dos espermatozoides, conforme relatos de Sanches et al (2009). Para essa avaliação, foi utilizado delineamento experimental inteiramente casualizado com três repetições para cada nível de contaminação por cádmio.…”
Section: Methodsunclassified
“…Após a ativação, 5 μL do material foram analisados em microscopia de luz (objetiva 40X), registrando-se o tempo transcorrido até a perda do movimento de 50% dos espermatozoides, conforme relatos de Sanches et al (2009). Para essa avaliação, foi utilizado delineamento experimental inteiramente casualizado com três repetições para cada nível de contaminação por cádmio.…”
Section: Methodsunclassified
“…Sanches et al (2009) reported that appropriate water volume for sperm activation guarantees significant increase in fertility rates. According to Chereguini et al (1999), the dilution volume of the fertilizing material has two important implications on fertility.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed semen samples from this pool. The spermatozoa concentration was determined by using cell counting in a Neubauer chamber ; the membrane integrity was evaluated by using Eosin-Nigrosin staining (adapted from BLOM, 1950); and the duration of spermatic motility was determined by measuring the time interval from the start of spermatic activity until <50% of spermatozoa remained motile (SANCHES et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Immediately after artificial fertilization, we analyzed a second sperm sample, to determine the duration of spermatic motility (SANCHES et al, 2009); this was considered as the time interval from the start of spermatic activity until 50% of the spermatozoa remained motile. The experimental design was identical to that mentioned, but the pH values were adjusted to 4.19, 5.49, 7.13, 8.35, and 9.89.…”
Section: Methodsmentioning
confidence: 99%